Research on battery to ride comfort of electric bicycle based on multi-body dynamics theory - Wenhua Du; Dawei Zhang; Xingyu Zhao (2009 IEEE International Conference on Automation and Logistics, 2009)
Based on multi-body dynamics theory and vibration theory, the dynamic performance of electric bicycle is simulated. Firstly, a two-dimensional mathematical model for the motion of a driver-electric bicycle coupled system was developed. The driver model is established by LifeMOD software which includes 19 skeletons, 18 joints and the electric bicycle model is built by virtual prototyping technology using the software of MSC, ADAMS. Secondly, an experiment test is taken to validate the feasibility of the model. Finally, the influence of the mass and installation location of battery to ride comfort was discussed. The result shows that the ride comfort is better as the mass of battery increased. When the mass of battery is lower, the installation location does little influence to ride comfort, but as it is bigger, the influence is remarkable. Consideration both the values of weighted accelerations RMS at the seat and hand, to the prototype electric bicycle, battery installed under the seat-tube has the better ride comfort.